2012
DOI: 10.1901/jaba.2012.45-585
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Inappropriate Social Interactions in Students With Asperger's Syndrome

Abstract: We analyzed the inappropriate social interactions of 3 students with Asperger's syndrome whose behavior was maintained by social positive reinforcement. We tested whether inappropriate social behavior was sensitive to social positive reinforcement contingencies and whether such contingencies could be reversed to increase the probability of socially appropriate responding. Our results show that social positive reinforcers can be identified for inappropriate social interactions and that appropriate social behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…Consistent with previous findings (Fisher et al, 2013; Frea & Hughes, 1997; Noel & Rubow, 2018; Rehfeldt & Chambers, 2003; Roantree & Kennedy, 2012), speech content among these participants was sensitive to changes in behavioral contingencies using differential attention as a reinforcer. This result suggests that the problematic speech of individuals with developmental disabilities could result from how conversation partners respond to the content of their speech in conversations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous findings (Fisher et al, 2013; Frea & Hughes, 1997; Noel & Rubow, 2018; Rehfeldt & Chambers, 2003; Roantree & Kennedy, 2012), speech content among these participants was sensitive to changes in behavioral contingencies using differential attention as a reinforcer. This result suggests that the problematic speech of individuals with developmental disabilities could result from how conversation partners respond to the content of their speech in conversations.…”
Section: Resultssupporting
confidence: 89%
“…Said another way, the individual may have experience engaging in both appropriate and inappropriate communicative behavior, but their history of reinforcement has favored more inappropriate communicative behavior. Such an approach has been characterized by first conducting a functional analysis of challenging conversational behavior and subsequently leveraging relevant antecedents and consequences to develop more appropriate communicative patterns (Fisher et al, 2013; Frea & Hughes, 1997; Noel & Rubow, 2018; Rehfeldt & Chambers, 2003; Roantree & Kennedy, 2012). For example, Rehfeldt and Chambers (2003) reported on an individual diagnosed with ASD who repeatedly talked about sirens, alarms, or medical appointments, which was found to be maintained by eye contact and reciprocal statements.…”
mentioning
confidence: 99%
“…Researchers could use examples of modified FA methodology as a model for how to conduct assessments with typical adult populations. For example, Roantree and Kennedy () assessed the function of inappropriate social behavior exhibited by three children with Asperger syndrome. The authors manipulated the delivery of peer attention following inappropriate social behavior using a trained peer confederate across two test conditions and a control condition, and differential responding was observed across conditions for all three subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Uncovering the behavioral processes that influence the presentation of restricted interests may be a necessary step toward understanding nonadherence and, therefore, designing interventions that promote adherence (Allen & Warzak, 2000;Stocco & Thompson, 2015). Although studies have reported effective interventions for excessive speech about restricted topics (Fisher et al, 2013;Kuntz et al, 2020;Lepper et al, 2017;Noel & Rubow, 2018;Rehfeldt & Chambers, 2003;Roantree & Kennedy, 2012;Stewart et al, 2007;Stocco et al, 2021), adherence to interventions has not been evaluated. These results suggest that adherence might depend on behavioral sensitivity to escape from uninterested listener responses.…”
Section: Discussionmentioning
confidence: 99%